Nearest Neighbor Heuristic Minimizes Logistics Distribution Distance And Travel Time: Metode Heuristik Nearest Neighbor Meminimalkan Jarak Dan Waktu Tempuh Distribusi Logistik - Naufal Akmal Christiono; Dewi Komala Sari (Proceedings of The ICECRS, 2024)
General Background Supply chain systems require strategic management to distribute production outputs continuously and accurately to consumers. Specific Background PT. Laprint Jaya experiences fluctuating shipping volumes and limited delivery fleets, causing complex Single Depot Capacitated Vehicle Routing Problems during dense daily schedules. Knowledge Gap Traditional routing decisions often fail to overcome fleet limitations and geographical complexities, requiring a practical technology approach to determine the shortest continuous paths. Aims This study analyzes optimal shipping routes regarding physical span and duration using the Nearest Neighbor method. Results Implementing this specific approach successfully cut the delivery span by 25 kilometers and reduced the total duration by 35 minutes compared to the initial manual routing procedures. Novelty This research demonstrates the practical integration of the Nearest Neighbor algorithm with digital maps to solve multi-point manufacturing product distribution problems. Implications Adopting this routing strategy facilitates supply chain management in determining optimal shipping operations, avoiding delays, and maximizing overall operational sustainability. Highlights: The Single Depot Capacitated Vehicle Routing Problem occurs due to fluctuating shipping volumes and restricted fleet capacities. Digital map integration identifies the shortest continuous paths for complex delivery schedules. Optimized shipping operations successfully cut 25 kilometers and saved 35 minutes from the initial route. Keywords: Vehicle Routing Problem, Supply Chain Management, Delivery Route Optimization, Heuristic Algorithm, Operational Efficiency